Perancangan Sistem Informasi Data Supplier Barang menggunakan Framework Ionic (Studi Kasus: CV. Delapan Sepuluh Cemerlang) - Adisattrio, Yefta; Susetyo, Yeremia Alfa (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Delapan sepuluh Cemerlang is a company engaged in the provision of goods, accuracy and speed are services that are needed to satisfy clients from CV. Delapan sepuluh Cemerlang, so an accurate information system is needed to get a price comparison of each item ordered by the client. This study aims to build an information system that can be easily accessed via a smartphone, the system was developed using the SDLC prototype method which was built using the Ionic framework specifically to be able to build systems with the help of HTML, CSS and AngularJs combined with firebase to make it easier and faster to change data on the system. System testing will use the functional suitability instrument with the Guttman scale as a measure.